2011
DOI: 10.2753/ree1540-496x470205
|View full text |Cite
|
Sign up to set email alerts
|

Heaping in Reported Earnings: Evidence from Monthly Financial Reports of Taiwanese Firms

Abstract: Heaping is a phenomenon in which reported numbers tend to appear in increments that are important for cultural or other reasons. This study reports that heaping is present in monthly earnings reports for publicly listed companies in Taiwan. We find that Taiwanese firms tend to report monthly earnings in increments of 5 in the first two places (digits) of the earnings numbers. Furthermore, we observe predominantly more zeros in the third through fifth places of monthly earnings numbers, suggesting that monthly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…The proportion of nines was 2.34% lower than expected, and the Z statistic was 1.77. This result concurs with the findings of prior studies (Carslaw, 1988;Thomas, 1989;Herrmann and Thomas, 2005;Lin et al, 2011) and suggests that window dressing is a pervasive phenomenon. Fewer zeros and more nines are expected in the second digit for firms reporting losses than for firms reporting a profit.…”
Section: Test Of Hypothesissupporting
confidence: 83%
See 1 more Smart Citation
“…The proportion of nines was 2.34% lower than expected, and the Z statistic was 1.77. This result concurs with the findings of prior studies (Carslaw, 1988;Thomas, 1989;Herrmann and Thomas, 2005;Lin et al, 2011) and suggests that window dressing is a pervasive phenomenon. Fewer zeros and more nines are expected in the second digit for firms reporting losses than for firms reporting a profit.…”
Section: Test Of Hypothesissupporting
confidence: 83%
“…A deviation in actual data from these expected frequencies indicates the presence of manipulation (Thomas, 2012). Benford's law has recently become an accepted tool, in both academic literature and practice, for the identification of contrived data (Carslaw, 1988;Thomas, 1989;Herrmann and Thomas, 2005;Lin et al, 2011;Reddy and Sebastin, 2012;Thomas, 2012). Rodriguez (2004) provided empirical evidence that, in the absence of earnings manipulation, corporate earnings follow Benford's law.…”
Section: Benford's Law and Earnings Managementmentioning
confidence: 99%
“…For example, data errors have been used to predict the accuracy of modern financial reports, where the over-reporting of some numbers and digits appears to be correlated with eventual revisions to financial statements. Numbers that seem to be rounded off are more likely to be deemed inaccurate and later revised (Lin, Guan, and Fang 2011). Similarly, Benford's law, which describes the distribution of first digits in most samples, has been used to uncover fraud in everything from financial reports to clinical trials to election data (Nye and Moul 2007;Rosentrater 2017;Miller 2015).…”
Section: Quantifying Quantitative Managementmentioning
confidence: 99%
“…Recent empirical research has found that the producers of earnings numbers (for example, corporate managers and financial analysts) appear to be likely to employ psychological heuristics when managers face uncertainty about future firm performance (e.g., Lin et al 2011). This could be taken as evidence that a firm is overvalued when it records high accruals and that the firm's stock price will perform poorly when these accruals are high (Hirshleifer 2001).…”
mentioning
confidence: 99%
“…Previous studies examined this relationship at the investor-portfolio level rather than at the level of each investor's stock returns (Bhattacharya et al 2012). Second, although studies have provided evidence of managerial efforts to round earnings numbers (Lin et al 2011), the conclusions drawn from these studies are based on conjecture with regard to window dressing and Benford's law rather than direct tests of the relationship between investors' stock returns and earnings management. Third, by comparing the samples in studies of investor portfolio returns with the sample used in the current study, we reveal that Taiwan investors trade more actively or aggressively than American, Swedish, and New Zealand investors.…”
mentioning
confidence: 99%